FACULTY ENACTMENT OF HIGHER EDUCATION CURRICULUM AND TEACHING POLICY IN KAZAKHSTAN: AN ETHNOGRAPHIC STUDY - Yeszhanova, Saule (Nazarbayev University Graduate School of Education, 2025)
For the past three decades Kazakhstan has undergone many transformations in the higher education system (Ahn et al., 2018). In particular, Kazakhstan’s universities have witnessed significant changes in the content of curriculum (Kerimkulova & Kuzhabekova, 2017). For example, Kazakh education policymakers asked the teaching body to modernise the content of the curriculum and change the way in which faculty work by aligning curriculum and the way they work with the Bologna process (Maudarbekova & Kashkinbayeva, 2014). However, no studies have been done on how faculty members enact curriculum reforms in practice in the Kazakh higher education system. Therefore, this ethnographic study explores how faculty members of one foreign languages department are implementing changes in curriculum and teaching policy introduced in Kazakhstan’s public higher education system, analysing their perspectives and experiences in changing their teaching and learning practices. Data were collected over a period of one semester from January to June, 2023 through semi-structured and informal interviews, classroom observations, faculty meetings, document analyses, and field notes involving 21 faculty members in one public university in Kazakhstan. My interpretation of the findings was the interplay of constraints and agency in curriculum reforms. It was revealed that faculty adhered to the authority of the Ministry of Higher Education and Science and university leadership, largely through compliance with external and internal regulations and documents. The findings also manifested that the institutional culture, marked by a top-down approach, constant oversight, frequent inspections, heavy workloads, and time constraints, hindered reforms by promoting a culture of compliance. In addition, financial limitations, lack of support from university administration, and inadequate infrastructure also impeded policy implementation. Despite these obstacles, faculty agency driven by teacher dedication, beliefs, professional development, peer collaboration, individual efforts, past and new teaching experiences, as well as their social and professional environments contributed to professional growth and facilitated the successful adoption of policies. The research findings of this study contribute to new knowledge by expanding the international literature on faculty agency within highly controlled systems and limited literature on higher education curriculum and policy implementation in Kazakhstan. The findings of this study offer important information for the policymakers and faculty members to facilitate the introduction of curriculum and teaching policy in practice.
Keywords: type of access: gated access; Faculty Enactment; Curriculum Management; Faculty Agency